A first peek into sub-picosecond dynamics of spin energy levels in magnetic biomolecules. Issue 21 (13th May 2019) - Rosaleny, Lorena E.; Zinovjev, Kirill; Tuñón, Iñaki; Gaita-Ariño, Alejandro
Abstract : Molecular dynamics and crystal field analysis are combined to obtain information about the real-time interaction between the spin energy levels and the dynamics of the molecular structure, at all relevant time scales. Abstract : We estimate the time- and temperature-evolution of spin energy levels in a metallopeptide by combining molecular dynamics with crystal field analysis. Fluctuations of tens of cm −1 for spin energy levels at fs times gradually average out at longer times. We confirm that local vibrations are key in spin dynamics.